Production of yams: present role and future prospect - Hahn, S.K.; Osiru, D.; Otoo, J.; Akoroda, M.O. (1995)
Yam is an important food crop, especially in the ‘yam zone' of West Africa. Total world production is about 20-25 million ton per annum, some 70 per cent of it grown in Nigeria. Although regarded mainly as a source of carbohydrate, some species are nearly as rich in protein as rice or maize.